Cage Culture in Iraq, Current Status & Potential: A Review - Nader A. Salman; Khalil I. Saleh; Majid M. Taher (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2022)
The present investigation aimed at discussing the present status of cage culture in Iraq and its future potential. Iraqi water resources can provide the basic requirements for successful fish culture in cages. Environmental conditions may maintain sustainable growth rate for 10 months at least. This has encouraged the investors and fish culturists to adopt such technique and make use of its advantages. Development of cage culture in Iraq has been reviewed from the early seventies till now. Fish production from cage culture was analyzed focusing upon recent developments in terms of fish consumption criteria and the per capita in Iraq. The floating cages culture system is considered now as the main culture system, because environmental conditions are suitable for cage culture more than the earthen ponds and recirculating systems. Cage culture industry relies on row materials that are locally available. They includes, frames, bridges, passage ways, nets, floating materials, feeders and wave breakers. Most of the cage units are locally manufactured from steel or wooden frame in square or rectangular shapes. Some circular and octahedral units are used in Kurdistan and Mosul. Researches on cage culture continued to optimize parameters such as stocking density, feeding and stocking sizes, stocking density of fish in the cages was fixed at 60-70 fish per m3 or 1500-2000 fish per cage of 1.5 x 4 x 4m using fish of 100 g in weight. Problems facing cage culture in Iraq are summarized by high prices of feeds, viral infection and other fish diseases, deterioration of water quality, the policy of importing fish from neighboring countries and lack of skills among farmers. Solutions for the above problems and recommendations for future development are discussed at the end of the article.